Fungsi Jaminan Sebagai Penentu Credit Scoring Dalam Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi - Nalendra Pradipto (Faculty of Law, Universitas Airlangga, 2021)
AbstractThe growth of information technology or commonly referred to as Industrial Revolution 4.0 has given birth to a new idea namely Money Lending and Borrowing Services based on Information Technology. Peer to Peer Lending (P2P) Lending is a service that is much in demand by the public. The majority of P2P Lending financial technology providers do not require collateral. With this condition, OJK has issued a special regulation, namely POJK No. 77 / POJK.01 / 2016 concerning Money Lending and Borrowing Services based on Information Technology. Article 21 POJK No.77 / POJK.01/2016 states that the Operator is required to manage credit risk and operational risk. One risk management undertaken by the Provider is to use Credit Scoring to classify Debtors into certain risk grades. However, because the majority of P2P Lending does not require a material guarantee, the Credit Scoring factor other than collateral becomes very important. In practice, the Operator is often less selective about the classification of Debtors in Credit Scoring, resulting in many defaults.Keywords: Peer to Peer Lending; Financial Technology; Credit Scoring; Risk Grade.AbstrakPerkembangan teknologi informasi informasi atau yang biasa disebut dengan Revolusi Industri 4.0 telah melahirkan gagasan baru yaitu Layanan Meminjam Uang Berbasis Teknologi Informasi. Peer to Peer Lending (P2P) Lending menjadi layanan yang banyak diminati oleh masyarakat. Dari beragam Penyelenggara teknologi finansial P2P Lending mayoritas tidak mensyaratkan adanya jaminan kebendaan. Dengan adanya kondisi tersebut OJK telah mengeluarkan aturan khusus yaitu POJK No. 77/POJK.01/2016 tentang Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi. Pasal 21 POJK No.77/POJK.01/2016 menyatakan Penyelenggara wajib melakukan manajemen risiko kredit dan risiko operasional. Salah satu manajemen risiko yang dilakukan Penyelenggara adalah menggunakan Credit Scoring untuk mengklasifikasi Debitor ke dalam risk grade tertentu. Meskipun demikian karena mayoritas P2P Lending tidak mensyaratkan adanya jaminan kebendaan, maka faktor Credit Scoring selain jaminan menjadi sangat penting. Pada prakteknya Penyelenggara seringkali kurang selektif terhadap klasifikasi Debitor dalam Credit Scoring sehingga banyak terjadi wanprestasi. Kata Kunci: Peer to Peer Lending; Teknologi Finansial; Credit Scoring; Risk Grade.